Impact of Mental Health on Academic Performance: A Study on the Risk of Failure in Higher Education - Inquilla-Mamani, Juan; Quispe, German Belizario; Chaiña-Chura, Fermín Francisco; Flores-Mamani, Emilio; Apaza-Ticona, Jorge; Incacutipa-Limachi, Duverly Joao (Journal of Ecohumanism, 2024)
Building healthy spaces and adequate mental health in the university context is of vital importance for optimal, quality and warm academic development, both for students and teachers. The purpose of the research is to determine the state of mental health of students as a risk factor for academic failure in higher education. For the methodological procedure, the “GHQ-28 Mental Health Assessment Scale and Questionnaire” was applied and a socio-educational form was used to measure academic performance. The level of mental health of students was estimated by applying the principal component factor analysis (PCA). To determine the variance of the factor analysis, Bartlett’s sphericity test was used, then the factorization process was carried out by the PCA method with a varimax rotation. They were selected for the sample by the simple random method, resulting in a total of 212 cases. The results obtained revealed that the “mental health status” variable has a significant effect on academic risk, with an estimated coefficient of -0.0878 and an associated p-value of 0.014. This indicates that as the mental health status of students decreases, an increase in the probability of repeating the academic semester is observed.